Tribological assessment of NiCr, Al2O3/TiO2, and Cr3C2/NiCr coatings applied on a cylinder liner of a heavy-duty diesel engine. (July 2021) - Biyiklioğlu, Onur; Tat, Mustafa Ertunc
Internal combustion engines consume about 90% of fuel refined from crude oil which supplies 30% of the annual global flow of energy. Heavy-duty diesel engines are the primary source of power used in highways, marine, railroads, and power stations. The right coating can improve the tribological properties of cylinder liners and increase the mechanical efficiency of an engine. Also, it can help to extend the maintenance periods, and enhance the reliability of the vehicles. In this research, tribological and economic evaluations were performed for coated and uncoated substrates from a cylinder liner of a heavy-duty diesel engine, aiming to lower friction, wear rate, and maintenance cost. A reciprocating friction test was conducted under dry condition using Wolfram carbide (tungsten carbide) ball applied a 10 N normal load on a ball on disk geometry. The cylinder liner was made of gray cast iron, and the substrates obtained were coated with three different coating materials (Cr3 C2 /NiCr, NiCr, and Al2 O3 /TiO2 ) through the thermal spray and high-velocity oxy-fuel coating process. Tribological evaluations showed that the substrates coded with Al2 O3 /TiO2 and Cr3 C2 /NiCr had the lowest friction coefficient and wear rate. The most economical coating was Al2 O3 /TiO2, being able to supply about 61% lower coefficient of friction and 94% less wear rate relative to the uncoated sample, for the price of one-third of the Cr3 C2 /NiCr coating and one half of a new gray cast iron cylinder liner.